(untitled) (Medico Legal Update, 2023)
Background: Regular epidemiological investigations are essential for gaining insights into the incidence of poisoning in various geographical areas. The purpose of this study was to assess the characteristics and trends of deaths due to poisoning in Gandhi Medical College, Secunderabad. Methods: Hospital records, inquest reports, post-mortem reports and toxicological analysis reports were analysed among various age groups, sex, type and manner of poisoning. Snake bite poisoning cases were excluded. Results: Out of 318 cases, we got positive toxicological analysis report for 287 (90.2%) cases. In our study predominance of male cases 259(81.45%) compared to female cases 59(18.55%) reported. In the age group most involved was 21-30 yrs 107 cases (34%) followed by 31-40 yrs 82 (26%), 41-50 yrs 49 (15%). Organophosphate poisoning reported in high number of cases 189(65.85%) followed by paraquat poisoning 44(15.33%), tablet poisoning 23(2.01%), Sulphuric acid poisoning 22(7.67%) and others 9 (3.14%) (Rodenticide, phenol, pyrethroid, nitrite). In manner of death suicidal cases 311(97.80%) reported more followed by accidental cases 7 (2.20%). In suicidal cases, economic constraints as a reason were outnumbered 209 cases (67.20%) followed by health issues 52(16.72%), academic failure 35(11.25%), love failure 15(4.82%). In region wise, rural areas reported more cases 244(76.73%) when compared to urban area 74 (23.27%). In season wise, more cases reported in April to July 148 cases (46.50%) followed by December to March 97 cases (30.5%), August to November 73 (23%). Zero homicidal poisoning noted. Conclusion: Organophosphate poisoning in active male population of rural areas with economic constraints were reported to be predominant.